Determination of Dynamic Mechanical Properties on Addition of Carbon Black-Nanosilica Hybrid Fillers in NR-SBR Blends with Special Reference to Power Transmission Belt Applications - Thuruthil Raju Aswathy; Seshadri Mohan; Thangavel Kalaivendhan; A. Mohammed Adhil (International Journal of Polymer Science)
Next to tyres, power transmission belts are one of the most complicated rubber products which is having a constant increase for demand in the market. Due to this high demand along with the requirement to meet certain special operating conditions, it is necessary to improve the belt properties continuously. In the last few decades, nanotechnology evolved as a suitable method for enhancing the properties of various rubber products without impacting the environment. Nanofillers which are having unique morphology along with excellent properties help to reduce the dependency in petroleum products and in turn make the products more sustainable. Even though, studies related to the usage of nanotechnology in the power transmission belt division are very limited. So, in this study, the effect of nanosilica on the dynamic mechanical properties of the natural rubber- (NR-) styrene butadiene rubber (SBR) blends is thoroughly studied with special reference to power transmission belt applications. The developed composites were analysed to ensure the rheological, mechanical, and morphological properties in comparison with the controlled samples. The nanosilica-based belt properties were analysed in reference with regular carbon black-filled belts, and a 15% improvement in belt life was obtained for newly developed belts.